Quality of Life of Patients Treated With Implant-Supported Mandibular Overdentures Evaluated With the Oral Health Impact Profile (OHIP-14): a Survey of 58 Patients - Ritva Kuoppala; Ritva Näpänkangas; Aune Raustia (eJournal of Oral Maxillofacial Research)
Objectives: The purpose of this study was to evaluate the oral health-related quality of life of patients treated with implant-supported mandibular overdentures and to compare the attachment systems used.Material and Methods: Altogether 112 patients treated with implant-supported mandibular overdentures in 1985 - 2004 were invited to the follow-up; 58 of them attended and replied to the Oral Health Impact Profile (OHIP-14) -questionnaire. There were 48 overdentures with a bar connection and 10 with a ball connection, the total number of implants installed and still in use was 197. The mean follow-up time was 13.7 years. The associations between the OHIP-14 variables and the patient’s age, gender as well as the number of implants supporting the overdenture and the type of attachment used were assessed.Results: The results showed that patients with implant-supported mandibular overdentures were satisfied with their oral health-related quality of life (OHRQoL). Older patients were more satisfied than younger ones in both genders. Neither the implant connection type nor the number of supporting implants seemed to have a significant influence on the OHRQoL.Conclusions: Especially older patients with mandibular implant-supported overdentures were satisfied with their oral health-related quality of life. Attachment type or the number of supporting implants did not have a significant influence on the oral health-related quality of life.